The Effect of Ultraviolet Treatment on TiO2 Nanotubes: A Study of Surface Characteristics, Bacterial Adhesion, and Gingival Fibroblast Response - Kobayashi Masahiko; Abdulmajeed Aous A.; Moon Jongyun; Shahramian Khalil; Punkkinen Risto; Shimada Jun; Vallittu Pekka K.; Lassila Lippo V. (MDPI, 2022)
Titanium dioxide (TiO2) nanotubes are emerging as a provocative target for oral implant research. The aim of this study was to evaluate the effect of UV on the wettability behavior, bacterial colonization, and fibroblast proliferation rate of TiO2 nanotube surfaces prepared using different anodization voltages and aimed for use as implant abutment materials. Four different experimental materials were prepared: (1) TiO2 nanotube 10 V; (2) TiO2 nanotube 15 V; (3) TiO2 nanotube 20 V; and (4) commercial pure titanium as a control group. TiO2 nanotube arrays were prepared in an aqueous electrolyte solution of hydrofluoric acid (HF, 0.5 vol.%). Different anodization voltages were used to modify the morphology of the TiO2 nanotubes. Equilibrium contact angles were measured using the sessile drop method with a contact angle meter. The investigated surfaces (n = 3) were incubated at 37 degrees C in a suspension of Streptococcus mutans (S. mutans) for 30 min for bacterial adhesion and 3 days for biofilm formation. Human gingival fibroblasts were plated and cultured on the experimental substrates for up to 7 days and the cell proliferation rate was assessed using the AlamarBlue assay(TM) (BioSource International, Camarillo, CA, USA). The data were analyzed using one-way ANOVA followed by Tukey's post-hoc test. Water contact angle measurements on the TiO2 after UV treatment showed an overall hydrophilic behavior regardless of the anodization voltage. The ranking of the UV-treated surfaces of experimental groups from lowest to highest for bacterial adhesion was: TiO2 nanotube 20 V < Ti and TiO2 nanotube 15 V < TiO2 nanotube 10 V (p < 0.05), and for bacterial biofilm formation was: TiO2 nanotube 20 V-TiO2 nanotube 10 V < Ti-TiO2 nanotube 15 V (p < 0.05). Fibroblast cell proliferation was lower on TiO2 nanotube surfaces throughout the incubation period and UV light treatment showed no enhancement in cellular response. UV treatment enhances the wettability behavior of TiO2 nanotube surfaces and could result in lower bacterial adhesion and biofilm formation.